The African National Congress' changing relationship with liberal democracy. - Brooks, Heidi (My University, 2007)
This dissertation traces the changing relationship of the ANC with liberal democracy from the party's inception to the present, and analyses the various influences upon, and shifts within, the ANC's thinking with regard to liberal democracy over this period. The paper argues that the years between 1987 and 1994 represented a critical and dramatic shift in the ANC's relationship with liberal democratic values in which it came to openly state its acceptance of institutionalised pluralism and rights. It also argues, however, that despite the momentous and extremely valuable nature of these commitments for the consolidation of liberal democracy in South Africa, there remain suggestions within the language and discourse of the ANC that are problematic for its full realisation, the essence of which lies in the ANC's own understanding and interpretation of the meaning of liberal democracy
Student Number : 0510823J - MA research report - School of Social Sciences - Faculty of Humanities
Keywords: changing relationship; ANC; liberal democracy; 1987; 1994; institutionalised pluralism; rights